California girls! - Martin, Ann M., 1955- (New York : Scholastic, 1990)
The Baby-sitters have won the lottery and the girls are going to California.
4.8
3-6
Keywords: Babysitters -- Fiction; Lotteries -- Fiction; Babysitters -- Fiction; Lotteries -- Fiction; California -- Fiction; California -- Fiction